2021
DOI: 10.1002/adma.202100429
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Selective Nitrogen Reduction via Geometric Coordination Engineering on Single‐Tungsten‐Atom Catalysts

Abstract: Atomic interface regulation that can efficiently optimize the performance of single‐atom catalysts (SACs) is a worthwhile research topic. The challenge lies in deeply understanding the structure–properties correlation based on control of the coordination chemistry of individual atoms. Herein, a new kind of W SACs with oxygen and nitrogen coordination (W‐NO/NC) and a high metal loading over 10 wt% is facilely prepared by introducing an oxygen‐bridged [WO4] tetrahedron. The local structure and coordination envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 38 publications
3
112
0
Order By: Relevance
“…A new strategy reported the use of direct atoms emitting from bulk metals, and subsequent trapping on nitrogen-rich porous carbon to form appropriate interactions between the metal atoms and supports. The central atom forms a coordination structure with other atoms, which changes the electronic structure of the central atom to increase its activity [22,23].…”
Section: Atomic Interface Regulation Affecting Metal Atoms and Supportsmentioning
confidence: 99%
“…A new strategy reported the use of direct atoms emitting from bulk metals, and subsequent trapping on nitrogen-rich porous carbon to form appropriate interactions between the metal atoms and supports. The central atom forms a coordination structure with other atoms, which changes the electronic structure of the central atom to increase its activity [22,23].…”
Section: Atomic Interface Regulation Affecting Metal Atoms and Supportsmentioning
confidence: 99%
“…Note that the structure models of experimental catalysts Mn–O 3 N 1 /PC 20 and W–N 2 O 2 /NC 21 were considered and excluded during the high throughput screening due to the rigid criteria (Δ G max < 0.5 eV) we set so as to obtain the eligible target catalysts with excellent performance.…”
Section: Resultsmentioning
confidence: 99%
“…After a comprehensive full reaction pathway search, we found that our calculated results on the structure models ( i.e. , Mn–O 3 N 1 @Gra and W–N 2 O 2 @Gra) of the experimental catalysts (Mn–O 3 N 1 /PC 20 and W–N 2 O 2 /NC 21 ) generally agree well with the experimental results even though the structure models (Mn–O 3 N 1 @Gra and W–N 2 O 2 @Gra) were excluded during high throughput screening under the rigid criteria of Δ G max < 0.5 eV. The detailed discussions, analyses, and comparisons between the experimental data and the calculated results on the structural models of experimental catalysts (Mn–O 3 N 1 /PC and W–N 2 O 2 /NC) are shown in the Appendix in last part of the supporting information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Electrocatalytic reduction of N 2 to NH 3 under ambient conditions has been regarded as a potential alternative to the energy and resourceintensive Haber-Bosch process. [8][9][10] However, the strong NN bond impedes the reduction of N 2 , which relies on efficient nitrogen activation. [11,12] Albeit noble metals exhibit a favorable NRR activity, their scarcity, and high cost restrict their application in large-scale nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%